2011
DOI: 10.1371/journal.pone.0014746
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 36 Expression Regulates Neuronal Differentiation from Neural Progenitor Cells

Abstract: BackgroundGap junction communication has been shown in glial and neuronal cells and it is thought they mediate inter- and intra-cellular communication. Connexin 36 (Cx36) is expressed extensively in the developing brain, with levels peaking at P14 after which its levels fall and its expression becomes entirely neuronal. These and other data have led to the hypothesis that Cx36 may direct neuronal coupling and neurogenesis during development.Methodology/Principal FindingsTo investigate Cx36 function we used a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 37 publications
(41 reference statements)
1
44
0
2
Order By: Relevance
“…In accordance, NPCs lacking Cx43 display reduced levels of P2Y 1 [174] and enhancement in b-catenin transcriptional activity [175], changes that are respectively accompanied by disturbed neuronal migration and increased differentiation. Of note, other Cx species, such as Cx26 and Cx36, may equally be involved in directing developmental neurogenesis [93,176]. Apart from channel-independent actions, HCs are suggested to modulate proliferative activity of NPCs by mediating spontaneous ICW propagation in the radial glial cell population in the VZ.…”
Section: General Concepts Of Connexin and Pannexin Signalingmentioning
confidence: 99%
“…In accordance, NPCs lacking Cx43 display reduced levels of P2Y 1 [174] and enhancement in b-catenin transcriptional activity [175], changes that are respectively accompanied by disturbed neuronal migration and increased differentiation. Of note, other Cx species, such as Cx26 and Cx36, may equally be involved in directing developmental neurogenesis [93,176]. Apart from channel-independent actions, HCs are suggested to modulate proliferative activity of NPCs by mediating spontaneous ICW propagation in the radial glial cell population in the VZ.…”
Section: General Concepts Of Connexin and Pannexin Signalingmentioning
confidence: 99%
“…For example, the connexin disruption of neural progenitors has been shown to reduce neuronal differentiation but increase glial differentiation. 61 Hence, cellular organization of EBs not only affected EB recovery, but also impacted differentiation potential postcryopreservation. Cellular redox state reflected by ROS generation is capable of balancing between self-renewal and differentiation of progenitor cells.…”
Section: The Microenvironment Of Ebs Regulated Cell Recoverymentioning
confidence: 99%
“…Cell differentiation is another important step in brain maturation; and, although information is lacking in the neocortex about the involvement of Cxs, experiments in striatal neurospheres have shown that neuronal and oligodendrocyte differentiation is partly mediated by gap junctions (Cx36; Hartfield et al 2011). This demonstrates the involvement of Cxs in all the major steps of cellular maturation.…”
Section: Principles Of Gap Junction Signalingmentioning
confidence: 99%